APAE de Francisco Morato e grupo multifamílias: um percurso de mudanças com base na teoria bioecológica - Palma Filho, João (2012)
This is a qualitative research based on Bioecological Theory, which aims at investigating how a set of multifamily actions can contribute to improving the quality of relations between APAE - Associação de Pais e Amigos dos Excepcionais (Association of Parents and Friends of Exceptional Children) in the city of Francisco Morato, and families of students with intellectual deficits, from the perspective of the eleven families participating. We seek to analyze whether these actions contributed to the families understanding the institution role and limits for the development of people with intellectual deficits, the possible emotional gains and improvement in interpersonal relationships with the children served by the institution. Eleven meetings were held with the multifamily group. Actions guided by the Bioecological Theory favored proximal processes, with communication conditions between the Multifamily Group and the Technical Team, so that the participants felt welcomed, expressed their feelings, doubts, and shared their personal experiences, becoming a cohesive and participatory group. Families commented: at the end, they had a deeper understanding of the work done at the institution; are more alert and able to devote more personal resources to care for their children; perceived the specialists are more aware of their observations. It was observed at the end of the research that multifamily activities and the care in building a communication path, propitiate the empowerment of families, which is fundamental to the educational process of children and young people with intellectual deficits